Effects of a novel schizophrenia risk variant rs7914558 at CNNM2 on brain structure and attributional style. - MORRIS, DEREK; DONOHOE, GARY; HARGREAVES, APRIL; GILL, MICHAEL; FAHEY, CIARA; CORVIN, AIDEN; TROPEA, DANIELA (My University, 2014)
BACKGROUND: A single nucleotide polymorphism (rs7914558) within the cyclin M2 (CNNM2) gene was recently identified as a common risk variant for schizophrenia. The mechanism by which CNNM2 confers risk is unknown. AIMS: To determine the impact of the rs7914558 risk 'G' allele [corrected] on measures of neurocognition, social cognition and brain structure. METHOD: Patients with schizophrenia (n = 400) and healthy controls (n = 160) completed measures of neuropsychological function and social cognition. Structural magnetic resonance imaging data were also acquired from an overlapping sample of Irish healthy controls (n = 159) and an independent sample of Italian patients (n = 82) and healthy controls (n = 39). RESULTS: No effects of genotype on neuropsychological test performance were observed. However, a dosage effect of the risk allele was found for an index of social cognition (i.e. attributional style), such that risk status was associated with reduced self-serving bias across groups (GG>AG>AA, P<0.05). Using voxel-based morphometry to investigate neuroanatomical regions putatively supporting social cognition, risk carriers had relatively increased grey matter volume in the right temporal pole and right anterior cingulate cortex (Pcorrected<0.05) in the Irish healthy controls sample; neuroanatomical associations between CNNM2 and grey matter volume in anterior cingulate cortex were also observed in the Italian schizophrenia and healthy controls samples. CONCLUSIONS: Although the biological role of CNNM2 in schizophrenia remains unknown, these data suggest that this CNNM2 risk variant rs7914558 may have an impact on neural systems relevant to social cognition. How such effects may mediate the relationship between genotype and disease risk remains to be established.
PUBLISHED
Keywords: Schizophrenia; Genes & Society; Neuroscience